A Mixed Reality Simulator Framework for 3D Object Optimization and Depth-of-Field Analysis - Mohamad Jamil; IIs Hamsir Ayub Wahab; Kiswanto Kiswanto; Seh Turuy (Universitas Nusantara PGRI Kediri, 2026)
Background: Mixed Reality (MR) technology enables real-time interaction between physical and digital environments and has become increasingly important in immersive simulation and visualization applications. However, MR implementation still faces challenges related to system performance limitations and the complexity of 3D object rendering, which may reduce immersion quality and interaction realism. Therefore, optimization of 3D assets and visual effects is urgently needed to improve MR efficiency and user experience. Objective: This study aims to propose a design and evaluation framework for Mixed Reality systems by focusing on 3D object optimization and Depth-of-Field (DoF) enhancement in Mixed Reality Simulator (MRSi) development. Methods: The proposed framework integrates vertex decimation-based 3D object optimization and DoF analysis using Circle of Confusion (CoC) calculations. Low-poly 3D assets were optimized through vertex and triangle reduction, while DoF parameters were adjusted based on focal length, aperture, and object distance. Results: The results showed that the proposed approach successfully reduced 3D model complexity by 16.280%–90.950% while maintaining visual quality, with CoC values ranging from 0.0066 to 0.2414, indicating improved depth perception and more realistic visual focus effects in MR environments. The optimization process improved rendering efficiency and enhanced visual realism in Mixed Reality environments. Conclusion: The proposed framework effectively improves MR system performance and immersion quality, providing practical guidance for the development of efficient and visually realistic Mixed Reality applications.